2020
DOI: 10.1159/000512631
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Testing for Fecal Calprotectin in Pediatric Gastroenterology Clinical Practice

Abstract: Gastrointestinal tract symptoms such as abdominal pain, constipation, diarrhea, and fever are frequent causes of visits to the pediatrician. The increasing prevalence of chronic gastrointestinal tract diseases, and the falling median age of their onset, indicate the need to identify new diagnostic methods that can differentiate inflammatory bowel diseases from other gastrointestinal tract conditions. A promising non-invasive and useful marker of intestinal inflammation is fecal calprotectin. The manuscript sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Another possible explanation for the absence of correlation between inflammation biomarkers and QoL in IBD may be that all patients included in this study were in clinical remission, thus excluding those with active disease, wherein inflammatory marker levels significantly elevate [ 4 , 5 ]. Finally, as proposed by Knisely and colleagues, the lack of correlation between biomarkers and patients could also be associated with cytokine gene polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation for the absence of correlation between inflammation biomarkers and QoL in IBD may be that all patients included in this study were in clinical remission, thus excluding those with active disease, wherein inflammatory marker levels significantly elevate [ 4 , 5 ]. Finally, as proposed by Knisely and colleagues, the lack of correlation between biomarkers and patients could also be associated with cytokine gene polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because of the sum of predisposing genetic and environmental factors such as diet, tobacco use, or stress at any given time [ 1 , 2 ]. Biomarkers such as C-reactive protein (CRP), faecal calprotectin (FC), or cortisol have been used to monitor inflammatory processes [ 3 ] and have proven very useful for diagnosing and monitoring IBD [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most effective method for diagnosis of IBD is endoscopy but it has the disadvantage of being invasive and costly [35] . On the other hand, Van de Vijver et al [36] demonstrated that endoscopy was not able to confirm the diagnosis of IBD in about 70% of patients and the accuracy of diagnosis was increased by detection of FC which is also noninvasive and a major inflammatory marker. Hence, FC is used as an indicator for IBD and serves as a diagnostic marker due to its resistance to degradation by pancreatic or intestinal secretions [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Диагностическая ценность кальпротектина у детей раннего возраста также вызывает растущий интерес. Повышенные концентрации кальпротектина в кале коррелируют с тяжестью воспалительных процессов при воспалительных заболеваниях кишечника [8,9], но могут встречаться и у здоровых новорожденных [10]. До настоящего времени существуют противоречивые данные о референсных значениях данного маркера у детей первого года жизни, не определена его роль у детей первого года с аллергической энтеропатией [11,12].…”
Section: Abstract: Food Allergy Non-invasive Monitoring Intestinal Ep...unclassified